Edirneli Âlî Hüseyin Çelebi’nin Ukûdü’l-Ukûlü (tahkik-inceleme) - Uzun, Aysun (My University, 2019)
EDİRNELİ ÂLÎ HÜSEYİN ÇELEBİ’NİN UKÛDÜ’L-UKÛLÜ(TAHKİK-İNCELEME)Bu çalışma, Yûsuf b. Tâhir el-Hûyî’nin Ferâ’idü’l-Harâ’id adlı eserinin ihtisârı ve Türkçe tercümesi olan Edirneli Âlî Hüseyin Çelebi’nin Ukûdü’l-Ukûl adlı eserinin inceleme ve tahkikidir.Edirneli Âlî Hüseyin Çelebi tarafından hicri XI. yy.’da kaleme alınan eser Arap dilinde yer alan mesellere dairdir. Eser, mesellerin alfabetik olarak tertip edildiği 29 bölümden oluşmaktadır. Çalışmanın giriş kısmında araştırmanın konusu, amacı ve yöntemi hakkında bilgi verilmiştir. İkinci bölümünde Arap dilinde emsâl ve emsâl kitapları; ikinci bölümünde Edirneli Âlî Hüseyin Çelebi’nin hayatı, eserleri ve Ukûdü’l-Ukûl incelenmiştir. Üçüncü bölümde ise Ukûdu’l-Ukûl’ün transkripsiyonlu metni neşredilmiştir.

UKUDU’L-UKUL OF EDİRNELİ ALİ HÜSEYİN ÇELEBİ (EXAMINATION AND CRITICAL EDITION)This study aims an examination and in depth analysis of an manuscript Ukûdu’l-Ukûl, originally written in Arabic by Yûsuf b. Tâhir el-Hûyî and called Ferâ’idü’l-Harâ’id, which is abbreviated and translated to Turkish by Edirneli Ali Hüseyin Çelebi.The manuscript written by Edirneli Hüseyin Çelebi in the 11st century of hegira is about Arabian proverbs. It consists of 29 chapter which is arranged in an alphabetical order. This study is divided mainly into an introduction and 3 parts. In the introduction, the topic, the purpose and the methodology of research have been provided. In the first part, Arabic proverbs and proverb books; and in the second part, the life and studies of Edirneli Âlî Hüseyin Çelebi and Ukûdu’l-Ukûl have been examined. Finally, in the last part the full transcription of Ukûdu’l-Ukûl has been given.
Keywords: Edirneli Âlî Hüseyin Çelebi; Ferâ’idü’l-Harâ’id; History; Kaynaklar; Mesel; Mesel Edirneli Âlî Hüseyin Çelebi; Sources; Tarih; Turkey; Türkiye; Ukûdu’l-Ukûl; Ukûdü’l-Ukûl